Recognizing Changes in Cognition in Sub Types of Acute Confusional State - Mushtaq, Raheel (JCDR Research and Publications (P) Limited, 2014)
Background: Delirium or acute confusional state is an acute neuropsychiatric syndrome, with varied cognitive dysfunctions. However, no comprehensive studies about this common condition have been carried out in India. Objectives: To assess cognitive dysfunctions in hypoactive and hyperactive delirium. Materials and Methods:Forty cases of delirium including hypoactive and hyperactive delirium and 40 other patients (neuropsychiatric patients) were studied as controls. Cognitive status estimation test, mini mental state examination and memorial delirium assessment scale were administered to each patient. All assessments were carried out three times in 24 hour cycle of day and night. The data was analysed using two sample independent t-test. Results: The mean age (standard deviation) of study and control group was 27.85 (13.73) and 33.10 (11.26) years respectively. 70% patients had hyperactive delirium while 30% were having hypoactive delirium. Hypoactive delirium had more cognitive impairment compared to hyperactive delirium (p=0.001). The difference between highest and lowest score of MMSE in both types of delirium (day to night) was found to be statically significant (p=0.001). Conclusion: The fluctuation in intensity of cognitive symptoms varies from day to night in both types of delirium, but more in hypoactive delirium and wider fluctuation in cognitive dysfunctions was noted in delirium cases with psychosis.